Dealing with unknown words in L2 reading: vocabulary and lexical inferencing strategies - Rousoulioti, Thomais; Mouti, Anna (Colombian Applied Linguistics Journal, 2016)
Vocabulary learning strategies constitute a subclass of language learning strategies which can be applied to the four language skills. The aim of the present study is to explore the vocabulary strategies adopted by adult learners of Greek as a second/foreign language when dealing with unknown words in L2 reading. To this end, the learners answered a questionnaire and so did their teachers. The results indicated that context and the general knowledge the learner of a second or foreign language brings with him/her about the topic—which is mainly supported by the other words in the sentence—play the most important role in understanding vocabulary. This conclusion probably confirms the power of the syntagmatic axis in the sentence, reinforcing mainly the holistic approach to be adopted in the classroom for the teaching of vocabulary. The process of triangulation has partially supported the research results.